Rekonfigurasi Kinerja Sektor Publik melalui Literasi Data Strategis: Model Operasionalisasi Berbasis Kompetensi dalam Kerangka Data-Driven Governance - Legito; Lubis, Muhammad Dicky Syahputra; Afni, Nurul (Jurnal Manajemen Sistem Informasi (JMASIF), 2026)
Digital transformation has reshaped public sector governance toward data-based decision-making that is measurable, accountable, and outcome-oriented. Data functions as a central foundation in planning, policy formulation, and performance evaluation. Such transformation requires strengthening strategic data literacy as a core competency of public officials in identifying, understanding, utilizing, communicating, and ethically reflecting on data use. This study applies a quantitative approach with an explanatory research design and Partial Least Squares–Structural Equation Modeling (PLS-SEM) using a hierarchical component model. Strategic Data Literacy is modeled as a third-order construct formed by five formative dimensions, while Public Sector Performance is measured reflectively through indicators of efficiency, effectiveness, and service equity. Empirical results indicate a positive and significant effect of strategic data literacy on public sector performance (β = 0.61; p < 0.001), with an R² value of 0.54. Data utilization and data understanding emerge as dominant dimensions in strengthening organizational analytical capacity. Findings demonstrate that a competency-based operationalization model supports the reconfiguration of public sector performance within a structured data-driven governance framework.